Revenue Budget Management Analysis and Village Shopping In Binuang Village Kec. Balusu District. Barru - Haerani Kahar (Journal GoodWill, 2023)
This research aims to investigate the management practices of Village Revenue and Expenditure Budget Financial Reports (APBDes) in Binuang Village, Balusu District, Barru Regency. The method used is a qualitative analysis method, which allows researchers to understand in depth the APBDes management practices and the qualitative aspects involved. The research results show that APBDes management in Binuang Village is based on the principle of transparency. This is reflected in the use of billboards or transparency boards, which provide detailed information regarding income, expenditure and financing listed in the APBDes. The existence of billboards or transparency boards helps the community to clearly understand the allocation of funds used by the village government. Apart from that, the research results also show that APBDes management practices in Binuang Village follow the principle of accountability. The reporting process for accountability in managing fund allocation is carried out regularly and in accordance with existing regulations. This shows that the village government is responsible for ensuring that the allocated funds are used appropriately and efficiently according to the needs and interests of the community. Thus, this research makes an important contribution to understanding APBDes management practices at the village level. These findings can be a basis for increasing transparency, accountability and efficiency in APBDes management in various other villages. Apart from that, this research also provides valuable information for local governments and other stakeholders to develop better policies in managing the APBDes to improve community welfare at the local level.